Сутність сучасного українського конституціоналізму - Крусян, Анжелика Романовна; Крусян, Анжеліка Романівна; Krusyan, Аnjelika R. (My University, 2010)
The democratic-legal essence of modern Ukrainian constitutionalism is grounded in the article. Democratism as the essence of constitutionalism is mediated by sovereignty of the people while maintaining balance between respect for the will of the majority, protection of minority rights and human rights and freedoms. The measure of democracy as an expression of the essence of constitutionalism is sovereignty of the people aimed at ensuring human rights and freedoms, recognition of his value and individual freedom that is possible only provided that sovereignty of the people is combined with the rule of law. The legal essence of constitutionalism is mediated by functional-instrumental significance and the role of law which has an instrumental value in establishing the legal foundations of constitutionalism. In addition, law is the power (the rule of law), which allows to restrict public power, because limitless power can suppress human rights, thereby annulling humanistic foundations of constitutionalism.
Крусян А. Р. Сутність сучасного українського конституціоналізму / А. Р. Курсян // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2010. – Т. 9. – С. 308-317.
Keywords: конституціоналізм; Конституція України; право; демократизм; демократично-правова сутність; конституционализм; Конституция Украины; демократически-правовая сущность; constitutionalism; constitution; law; demokratism; democratic-legal esence